Immune surveillance by autoreactive CD4‐positive helper T cells is a common phenomenon in patients with acute myeloid leukemia. (6th September 2018) - Lam, Tin Sing; van de Meent, Marian; Marijt, Erik W. A.; Falkenburg, J. H. Frederik; Jedema, Inge
Abstract: Objectives: The importance of autologous T‐cell responses in immune surveillance against acute myeloid leukemia (AML) remains unclear. Therefore, we investigated the presence and functional reactivity of autoreactive T‐cell responses against autologous AML blasts. Methods: T cells purified from PB samples harvested from patients during first complete remission were stimulated with autologous AML material harvested at diagnosis. After 12‐14 days of coculture, the T cells were restimulated with autologous AML cells, and leukemia‐reactive T‐cell clones were isolated based on their expression of the activation marker CD137. Results: We demonstrated that AML‐induced autoreactivity was predominantly mediated by CD4 T cells. These autoreactive T cells showed abundant cytokine production, coincided by modest cytotoxic activity. Upon coculture, the autoreactive T cells were able to increase the immunogenicity of the AML blasts. Interestingly, similar AML‐directed reactivity was observed using HLA‐identical responder T cells from healthy donors. Conclusions: We demonstrated that the presence of AML‐directed autoreactive T cells is a common phenomenon which appears to be part of the general T‐cell repertoire also in healthy individuals. This autoreactive AML‐directed T‐cell response may directly contribute to anti‐AML immune surveillance especially in the situation of minimal residual disease, but furthermore the immune‐modulatory effect on the AML phenotype may pave the way for other immunological interventions.